Health and behavioral factors associated with binge drinking among university students in nine ASEAN countries - Siyan Yi; Chanrith Ngin; Karl Peltzer; Supa Pengpid (Substance Abuse Treatment, Prevention, and Policy, 2017)
Abstract Background Heavy drinking among university students has been globally recognized as a major public health burden. In the Association of Southeast Asian Nations (ASEAN) region, studies on this issue have been scant, country-specific and in different time frames. The aim of this study was to identify social and behavioral factors associated with binge drinking among university students in nine ASEAN countries. Methods This cross-sectional study was conducted in 2015 among 8809 undergraduate university students from 13 universities in Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand and Vietnam using self-administered questionnaire. Multivariate logistic regression analyses were conducted to explore the associated factors. Results More than half (62.3%) of the study sample were female with a mean age of 20.5 (SD = 2.0) years. Of total, 12.8% were infrequent (<once per month) and 6.4% frequent (≥ once per month) binge drinkers. After adjustment, among males, higher binge drinking remained significantly associated with being in older age groups, living with parents or guardians, lower level of non-organized religious activity, lack of knowledge on alcohol-heart disease relationship, weak beliefs in the importance of limiting alcohol use, poor subjective health status, lower level of life satisfaction, tobacco and illicit drug use, depressive symptoms and high level physical activity. Among females, higher prevalence of binge drinking remained significantly associated with being in the older age groups, poorer family background, living in an upper-middle- or high-income country, lower level of non-organized religious activity, lack of knowledge on alcohol-heart disease relationship, lack of knowledge on alcohol-high blood pressure relationship, weak beliefs in the importance of limiting alcohol use, lower level of life satisfaction, use of other substances such as tobacco and illicit drug, depressive symptoms and high level of physical activity. Conclusions Findings from this study indicate a need for devising or refining university health promotion programs that integrate binge drinking, other substance use, co-occurring addictive behaviors and health beliefs in the respective countries.